PENGARUH MODEL PEMBELAJARAN GAME BASED LEARNING DENGAN BANTUAN MEDIA UNO STACKO FOR QUESTION CARD TERHADAP HASIL BELAJAR BAHASA INDONESIA TOPIK BAHASAN PUISI RAKYAT - Kusmiyati, Kusmiyati (sarasvati, 2021)
The use of still traditional learning models is one of the causes of the underdevelopment of students in terms of both values and interest in learning. Indonesian subjects that are supposed to be fun get boring if the learning model used is not appropriate. The game based learning model with UNO Stacko for question card media is one of the innovative learning models that teachers can use when learning Indonesian. This study aims to determine the differences in learning outcomes and to describe the effects of game-based learning models with the UN Stacko for question card media on Indonesian language learning outcomes for seventh grade students at MTS Darul Ulum Lamongan. This research is an experimental type of research with a quantitative approach. The sample of this research includes 2 groups of 7th grade students for the 2020-2021 academic year. Data collection techniques in the form of observations and tests. Based on the results of the analysis, it was concluded that there were differences in the learning outcomes of the Indonesian language in the group of students with the application of game-based learning models and in the groups of students with the application of conventional learning models and the application of this learning model influenced Learning outcomes of grade VII Indonesian students at MTS Darul Ulum Lamongan strong.